Subarachnoid hemorrhage due to rupture of very small aneurysms of the anterior part of the circle of Willis - P. G. Shnyakin; I. S. Usatova; A. V. Trubkin; I. A. Kazadaeva (Инновационная медицина Кубани, 2022)
Objective: To assess the frequency of ruptures of very small cerebral aneurysms, features of the perioperative period and outcomes, in comparison with the rupture of ordinarily sized aneurysms.Material and methods: A comparative analysis of the group of patients with ruptured cerebral miliary aneurysms (n = 18) and the group of patients with ruptured cerebral aneurysms of regular size (n = 308) was carried out. All patients underwent open surgery in the first 3 days after the rupture (osteoplastic craniotomy, microsurgical aneurysm clipping). We compared gender, age of patients, severity of the patient’s condition at the moment of admission, severity of subarachnoid hemorrhage, location of aneurysms, aspect ratio, duration of the operation, frequency of intraoperative ruptures, postoperative mortality.Results: It was found that miliary aneurysm rupture occurs in 5.5% of all patients with cerebral aneurysm rupture. The most common cases of rupture of very small aneurysms were in women (77.7%), with a mean age of 50.8 years. Aneurysms of the anterior communicating artery (66.6%) with a narrow neck (average aspect ratio – 2.1) were the most common. Patients with rupture of very small aneurysms were 7.9% more likely to be admitted in a state of subcompensation or decompensation (Hunt-Hess IV–V), they had massive subarachnoid hemorrhage (Fisher III) 19.6% more often than with ruptured aneurysms of regular size. On average, operations in cases of very small aneurysms lasted 30 minutes less than clipping of ordinary aneurysms, but were complicated by intraoperative rupture twice as often (38.8% and 16.5%, respectively). Postoperative mortality in the group of patients with ruptured miliary aneurysms was 5.7% higher than in patients with ruptured aneurysms of regular size.Conclusion: Rupture of cerebral miliary aneurysms is relatively rare. Women of 50–60 years old with very small aneurysms of the anterior communicating artery with a narrow neck constitute the main group of such patients. Massive subarachnoid hemorrhage and severe condition of patients on admission are more common with miliary aneurysms than with ordinarily sized aneurysms. The small size of the aneurysm and the work near the rupture determine the more frequent contact intraoperative rupture when the neck is exposed as compared to operations on larger aneurysms, which negatively affects the treatment outcomes in this group of patients.